(untitled) (Research, Society and Development, 2023)
Brazil has been showing a large increase in elderly people, and Alzheimer’s Disease (AD) affects about 1.2 million people. The disease affects memory, language and reasoning, causing a decline in autonomy and making decision-making difficult. The aim of this study was to identify the main difficulties encountered by family caregivers of a person with AD. This is an exploratory, descriptive research with a qualitative approach carried out with ten family caregivers of people with AD. Participants answered a questionnaire with 10 open questions about AD. The research was carried out in two Family Health Strategies in the city of Lajeado in Rio Grande do Sul. 10 women aged 26 to 63 years participated in this research. Regarding kinship, 09 were daughters and 01 was granddaughter. The information was presented through three thematic categories: "Difficulties faced by caregivers", "Main changes in the physical structure of the house and family dynamics" and "Caregivers’ health problems". All participants reported feeling some type of back pain and in the joints. They also reported difficulty sleeping, depressive symptoms, anxiety and lack of time for self-care. The main contribution of this study was to give visibility to caregivers of family members with AD. Thus, nursing interventions aim to promote the health of these caregivers to improve the quality of life and, consequently, improve the care provided to family members who are sick with Alzheimer’s.